Comparison of manual and femtosecond astigmatic keratotomy in the treatment of postkeratoplasty astigmatism. Issue 5 (30th October 2020) - Sorkin, Nir; Mimouni, Michael; Santaella, Gisella; Kreimei, Mohammad; Trinh, Tanya; Yang, Yelin; Saeed, Danyal; Cohen, Eyal; Rootman, David S.; Chan, Clara C.; Slomovic, Allan R.
Abstract: Purpose: To compare the outcomes of femtosecond astigmatic keratotomy (FSAK) and manual astigmatic keratotomy (AK) in treatment of postkeratoplasty astigmatism. Methods: A retrospective, comparative, pairwise‐matched case series including 150 patients who underwent either FSAK ( n  = 75) or manual AK ( n  = 75) for the treatment of astigmatism (>3.00 D) following penetrating keratoplasty or deep anterior lamellar keratoplasty. Pairwise matching for baseline variables (age, visual acuity and astigmatism) was performed. Results: Mean age was 57.5 ± 16.0 years. The FSAK group had significantly better postoperative best‐corrected visual acuity (BCVA) (p = 0.010), uncorrected visual acuity (UCVA) (p = 0.049), corneal astigmatism (p = 0.020) and manifest astigmatism (p < 0.001) compared with the manual AK group. Gain of ≥3 lines in BCVA (logMAR) was seen in five eyes (6.7%) and 21 eyes (28.0%) in manual AK and FSAK, respectively (p = 0.005). Alpins vector analysis showed lower (closer to 0) index of success (0.50 ± 0.24 and 0.79 ± 0.48, p < 0.001) and higher (closer to 1) correction index (0.94 ± 0.45 and 0.74 ± 0.55, p = 0.020) in FSAK compared with manual AK. Corneal and manifest astigmatism improved significantly in both groups, while BCVA and UCVA improved significantly in FSAK only. Repeat AK rate was 32% (24 eyes) in manual AK and 4% (three eyes) in FSAK (p < 0.001). Overcorrection‐related re‐suturing rate was 0% in manual AK and 8% (six eyes) in FSAK (p = 0.037). There was one microperforation (1.3%) in FSAK, and there were no occurrences of graft dehiscence, infectious keratitis or graft rejection. Conclusions: Both manual AK and FSAK were safe and effective in reducing postkeratoplasty astigmatism. FSAK had superior visual and keratometric outcomes compared with manual AK.